Location and Capacity Planning of Electric Vehicles Charging Piles. (May 2019) - Shimin, Yi; Yunlian, Sun; Xiaodi, Zhang; Ying, Wu; Jinlei, Hu; Qiwu, Zou; Xinlin, Xie; Bin, Fu
Abstract: As the planning and construction of electric vehicle charging pile plays a decisive role in the promotion of electric vehicles, this article puts forward a planning method considering the cooperation of different types of charging piles and analyzes the Residential and social charging piles. On the basis of determined number of charging piles in residential area, the planning of social charging piles is analyzed from the demand of charging considering the unbalance of electric vehicles' promotion, the location of charging piles considering the minimum charge distance and the capacity of charging piles considering the situation that EVs don't charge every day. And then the processes of planning are determined. Finally, the planning method is applied to a Xincheng planning in ZhuoZhou which could illustrate the feasibility of this method. Compared with other method, the method of this article pays more attention to the actual situation from the load forecast to the overall planning in the area, thus the result is more realistic and in line with the planning requirements.